Sosialisasi Hak Konstitusional Warga yang Terkena Dampak Bencana di Aceh Tamiang - Ismed Batubara; Arif Hadian; Yeltriana Yeltriana; Dalfatara Dalfatara; Nazwa Fitri (Indonesia Berdampak: Jurnal Pengabdian kepada Masyarakat, 2026)
This community service program takes the form of counseling on post-flood recovery and strengthening of children's education in Kuala Simpang, specifically through the "Sang Juara" tutoring program through the Education, Law, Sharia, and Economics (ELSE) approach on December 24, 2025. This Community Service Program (PKM) was implemented according to the established plan and is a concrete demonstration of the realization of the Tri Dharma of Higher Education, as mandated by the government to higher education institutions. Through participation packaged with education and outreach on the theme of "Education, Law, Sharia, and Economics (ELSE), the Community Service Program (PKM) with its educational and outreach approach fosters a spirit of recovery and recovery, evidenced by the responses of children affected by the disaster